Timbre-induced pitch shift from the perspective of Signal Detection Theory: the impact of musical expertise, silence interval, and pitch region - Vurma, Allan (Frontiers in Psychology, 2014)
The paradigm of Signal Detection Theory was used to analyze the ability of professional pianists (N = 16) and string players (N = 15) to discriminate small F0 differences between consecutive musical tones, presented in pairs, with identical and with different (bright and dull) timbres. The sensitivity (d’) and response bias (c) were heavily dependent on the timbral arrangement of the pairs of tones (the “comparable tones”), which can be interpreted as the influence of timbre-induced pitch shift on F0 discrimination. The participants were somewhat biased to ‘miss’ signals when comparable tones had identical timbres and to make ‘false alarms’ when the tones had different timbres. The d’ was lowest when the tones with a lower F0 in those stimulus-pairs containing tones with different timbres had a brighter timber, and highest when both tones had bright timbre. On average, the string players had a somewhat higher d’ and their perception was slightly less influenced by timbre-induced pitch shift when compared to the pianists. Nevertheless, the dependence of d’ and c on the timbral arrangement of the tones was registered in the case of all the participants at all the investigated pitch regions around D#3, D4 and C#5. Furthermore, the presence of a silence of 3.5 seconds – a silence interval – between the tones to be compared had an impact on both d’ and c values as well as on the degree of vulnerability to timbre-induced pitch shift.